Non-invasive assessment of left ventricular response to Valsalva manoeuvre in normal and diabetic subjects using praecordial accelerocardiography. Issue 2 (February 1979) - Hume, L; Ewing, D J; Campbell, I W; Reuben, S R; Clarke, B F
Abstract : The left ventricular response to the Valsalva manoeuvre was studied in 5 normal subjects (group 1), 6 diabetics without autonomic neuropathy (group 2), and 5 diabetics with autonomic neuropathy (group 3), using the maximum amplitude of the praecordial accelerocardiogram (DE) as a noninvasive index of left ventricular performance. During the Valsalva manoeuvre DE decreased in all 3 groups. In groups 1 and 2, DE increased significantly above the control value after release of the manoveuvre (DE overshoot) but this did not occur in group 3. It is suggested that the overshoot of DE in groups 1 and 2 reflects an increase in left ventricular contractility after release of the Valsalva manoeuvre and the absence of an overshoot in DE in the patients with autonomic neuropathy is the result of loss of cardiac adrenergic innervation. The ability to detect an abnormal cardiovascular response to the Valsalva manoeuvre using the non-invasive technique of praecordial accelerocardiography may be of practical value in the assessment of left ventricular function.